Contraception and Sexual and Reproductive Awareness Among Ghanaian Muslim Youth - Jibrail Bin Yusuf (SAGE Open, 2014)
Ghana, a lower-middle income country that is still grappling with fertility and birth rates, initiated family planning for the youth decades ago. This mainly targeted deprived communities, and the Muslim youth were also exposed to contraception. However, contraception awareness among the Muslim youth has had difficulties and repercussions. Against the social and economic challenges facing the Ghanaian Muslim youth, this article evaluates their awareness about contraception focusing on the issues and their ramification with the aim of identifying prospects for development. The findings reveal that awareness is high but not in a positive sense as the general patronage among couples is low, while among the unmarried, the awareness has negatively affected their morality. Among the issues, there is a disconnection between service providers and the community while some Muslims think that contraception can reduce the Muslim population and is un-Islamic. It was argued that contraception is permitted for Muslims provided there is ethical justification and that in view of the social and economic challenges, including school dropouts and Muslim child migration due to the poverty of parents, the Muslim youth must plan their childbirth. Hence, it was recommended that government must tackle the problem of education in Muslim communities. The Ulama should also dialogue with the service providers to create trust between the health providers and the Muslims.